2017
DOI: 10.1002/2016ja023508
|View full text |Cite
|
Sign up to set email alerts
|

Nightside ionosphere of Mars: Composition, vertical structure, and variability

Abstract: We provide an overview of the composition, vertical structure, and variability of the nightside ionosphere of Mars as observed by Mars Atmosphere and Volatile EvolutioN (MAVEN)'s Neutral Gas and Ion Mass Spectrometer (NGIMS) through 19 months of the MAVEN mission. We show that O 2+ is the most abundant ion down to ∼130 km at all nightside solar zenith angles (SZA). However, below 130 km NO+ is the most abundant ion, and NO+ densities increase with decreasing altitude down to at least 120 km. We also show how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 61 publications
(163 reference statements)
11
83
0
Order By: Relevance
“…The maximum dynamic pressure during the solar event in the present study is more than the peak dynamic pressure observed by MAVEN during the 8 March 2015 interplanetary CME event Thampi et al, 2018). The higher standard deviations for the nightside profile indicate that the nightside ionosphere of Mars is more variable compared to the dayside which corroborates with the previous observations (Girazian et al, 2017). (For the MAVEN data presented here, a new orbit number starts when the instrument is at the geometric periapsis, and is the same for the outbound and the next inbound sectors, and incremented at the next periapsis).…”
Section: Observationssupporting
confidence: 91%
“…The maximum dynamic pressure during the solar event in the present study is more than the peak dynamic pressure observed by MAVEN during the 8 March 2015 interplanetary CME event Thampi et al, 2018). The higher standard deviations for the nightside profile indicate that the nightside ionosphere of Mars is more variable compared to the dayside which corroborates with the previous observations (Girazian et al, 2017). (For the MAVEN data presented here, a new orbit number starts when the instrument is at the geometric periapsis, and is the same for the outbound and the next inbound sectors, and incremented at the next periapsis).…”
Section: Observationssupporting
confidence: 91%
“…Here we consider four ion species including O 2+, O + , HCO + , and NO + in decreasing order of nightside median density at 500 km, with the remaining species displayed in Figure neglected due to their relatively low densities at all altitudes sampled by the NGIMS. The nightside median density profiles for the four species are shown in Figure at 180–500 km, which are generally consistent with the published nightside NGIMS ion density results (e.g., Girazian, Mahaffy, Lillis, Benna, Elrod, Jakosky, et al, ; Girazian, Mahaffy, Lillis, Benna, Elrod, Fowler, et al, ). Except for regions above 450 km, these species roughly present an exponential decay with increasing altitude, though their density scale heights are not as constant as on the dayside.…”
Section: The Median Morphology Of the Martian Ionospheresupporting
confidence: 88%
“…The solar cycle variation in ion outflow was also obtained by Cravens et al () using a semiempirical approach and predicted to scale with the square root of the solar ionizing flux. The inferred dayside plasma outflow either helps to maintain a substantial nightside ionosphere on Mars (e.g., Brain et al, ; Cui et al, ; Girazian, Mahaffy, Lillis, Benna, Elrod, Jakosky, ; Němec et al, ; Withers et al, ) or leads to considerable plasma escape down the tail (e.g., Barabash et al, ; Dubinin, Fraenz, Pätzold, McFadden, et al, ; Dubinin, Fraenz, Pätzold, Andrews, et al, ; Edberg et al, ; Lundin et al, ; Ramstad et al, ). The relative contributions of these two channels are comparable based on existing magnetohydrodynamic calculations (e.g., Ma et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations